Penerapan Hukum Islam Dalam Peraturan Perundang-undangan di Indonesia - Ummi Najipah; Safitri, T. dela; Khasyi, Naura Muthia; Aisyah, Siti; Tami, Wilanda Juliani (Tabayyun : Journal Of Islamic Studies, 2025)
The process of developing Indonesia's national legal system involves a complex configuration of various issues of public interest and expectations, in which Islamic law plays a significant role as a source of law. There are several challenges in integrating Islamic law with the national legal system, such as differences in understanding of harmony with the basic principles and practical difficulties in its application. This research uses a normative approach with a literature method that focuses on the review of documents and literature related to the application of Islamic law in the Indonesian legal system. The purpose of this research is to examine more deeply the understanding of the interaction between Islamic law and principles, that Islamic law has a significant influence on the development of legal norms and principles in the Indonesian legal system. The findings of this study indicate that Islamic law has a significant influence on the development of legal norms and principles in the Indonesian legal system. Islamic law is one of the authoritative sources in the formation of national law, such as in the marriage law and the religious justice law.